Migration history of Avicennia marina populations: a legacy of mangrove expansion on the Sunda Shelf - Triest, Ludwig; Phan, Thi Thuy Hang; Luong, Quang Doc; Bousquet-Mélou, Anne; Do, Bich Thi Ngoc; Sierens, Tim; Dahdouh-Guebas, Farid; Koedam, Nico; Van der Stocken, Tom (Frontiers in Marine Science, 2025)
IntroductionMangrove forests maintain connectivity and stay genetically linked through ocean-dispersed propagules. Avicennia species exhibit a pronounced genetic structure following a stepping-stone migration model, with connectivity patterns linked to the strength and direction of ocean-surface currents. The present-day spatial genetic structure of Avicennia marina populations is an imprint of connectivity. This allows for estimating their migration history in relation to coastal configuration and Holocene sea-level rise. MethodsWe examined the genetic diversity, structure, and demographic and evolutionary history of the establishment of 10 A. marina sites across coastal stretches of Vietnam using nuclear microsatellite markers in 558 individual trees. Additionally, genome skimming of 24 samples allowed the detailed analysis of the complete chloroplast genome and nuclear ribosomal cistron sequences. Although A. marina grew mixed with Avicennia alba, a NewHybrids analysis ensured that only pure A. marina was considered in this study.ResultsMicrosatellites revealed an overall low allelic diversity, although inbreeding, recent bottlenecks, and the strong differentiation of populations were detected. Genetic breaks along the coast were confirmed through AMOVA, structure, and barrier analyses, while RST > FST indicated an evolutionary signal of divergence consistent with isolation by distance. migrate-n model tests and divMigrate analysis supported northward unidirectional stepping-stone migration history. Approximate Bayesian computation (ABC) demographic analysis indicated a Holocene expansion, whereas an origin model demonstrated discrete migration events across Vietnam, with southern populations most closely related to a bottlenecked ancestral population. A haplotype network considering complete chloroplast genomes revealed identical or nearly similar propagule sources of A. marina throughout central and northern Vietnam, thereby following the most recent Holocene expansion on the northwestern Sunda Shelf.DiscussionMicrosatellites, chloroplast, and rRNA cistron sequences confirmed the uniqueness of A. marina from the southernmost peninsula and their far relatedness with other populations in Southeast Asia, suggesting a longer-term persistence since gradual Shelf flooding. It is additionally proposed that, in addition to ocean currents, coastal landforms such as shallow areas with broad river delta plumes, a wide mouth, or strong discharge such as for the Mekong and Red Rivers may have caused a regional substructure and provided a quasi-permanent barrier to alongshore currents and mangrove connectivity. Perspectives on conservation issues of the species are provided.